2010
DOI: 10.1186/1757-1146-3-32
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations of muscle fibre cross sectional area of flexor digitorum brevis in cadaver feet with and without claw toes

Abstract: BackgroundIn order to facilitate normal gait, toes require to be in a rectus position during the propulsive phase. This requires a correct balance and sequence of activity of the intrinsic musculature of the feet. Alteration of this balance and sequence may lead to the development of claw toes. Atrophy of the lumbricals occurs in the development of claw toes, but it is not known if changes occur in any other intrinsic muscles, including flexor digitorum brevis. This study set out to investigate whether hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Tibialis anterior contracts in early stance to allow gradual plantarflexion of the foot and to decelerate downward motion of the foot. FHL and FDL further contribute to the maintenance of the MLA [16] but their actions are perhaps more coupled with intrinsic muscle and plantar fascia function than TP and TA, since all these structures insert into the digits [17,18]. However, the relationship between the extrinsic and intrinsic foot structures that share common functions has not been reported in pes planus.…”
Section: Introductionmentioning
confidence: 99%
“…Tibialis anterior contracts in early stance to allow gradual plantarflexion of the foot and to decelerate downward motion of the foot. FHL and FDL further contribute to the maintenance of the MLA [16] but their actions are perhaps more coupled with intrinsic muscle and plantar fascia function than TP and TA, since all these structures insert into the digits [17,18]. However, the relationship between the extrinsic and intrinsic foot structures that share common functions has not been reported in pes planus.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no published studies that have explored the association between foot posture and lower limb muscle and tendon morphology. Two studies have investigated differences in flexor digitorum brevis and longus muscle cross‐sectional area comparing individuals with claw and normal toes; however, these studies only investigated a small sample of cadaveric specimens (Semple & Baird, ; Locke et al., ).…”
mentioning
confidence: 99%
“… ). Further, some studies on cadaver feet showed that the muscular slip for the fifth toe, or for the fifth and fourth toes is much smaller and the tendons are thinner than that for the other toes 18 , 22 , 23 ) . Therefore, the flexor force applied to the PIP joint of the second, third, and fourth toes could be greater, thereby increasing the height of the second, third, and fourth metatarsal heads, respectively; the height of the first and fifth metatarsal heads did not increase.…”
Section: Discussionmentioning
confidence: 99%
“…FDB is a fusiform muscle originating from the medial calcaneal process and the plantar aponeurosis. At its distal aspect, it is divided into four parts, which gives rise to four tendons that insert into the lateral four toes on the plantar surface of the intermediate phalanx 18 ) . Anatomical muscle CSA and muscle volume are valuable predictors of muscular strength and power output 19 , 20 , 21 ) .…”
Section: Discussionmentioning
confidence: 99%